Análise da expressão da metalotioneína em duas espécies de peixes, Oreochromis niloticus e Prochilodus lineatus - Coimbra, Thaissa de Melo Galante (Universidade Federal de São Carlos, 2008)
Metallothioneins (MT) are non enzymatic proteins with with metal-binding ability. It has been used as a biomarker for environmental pollution by the analysis of its expression in several fish species. The tilapia is a commonly used model in studies of animal toxicology and some of these species have a well characterized MT sequence. Here, the Oreochromis niloticus specie was used in the standardization of the MT expression assay. The Prochilodus lineatus species is widely distributed in the Brazilian s Basins that has been studied regarding growth, illness and the toxicity of metals. However the MT DNA sequence from this species has not been described. The aim of this project was the analysis of the MT DNA in both species, O. niloticus and P. lineatus. For that, individuals from these species received intraperitoneal injections of zinc chloride, in increasing doses of 1 to 8 mg/kg for 4 days.. After this time, animals were killed and total RNA was isolated from the liver and used in an RT-PCR with primers designed accordingly to MT coding regions of fish MT deposited at www.ncbi.nlm.nih.gov. DNA sequencing confirmed the highly conserved MT sequence for both species. For quantitative analysis, cDNA was used in a similar real-time PCR with the same primers plus the fluorophore Syber Green. TheZnCl2 treatment increased MT mRNA expression about 4 times for O. niloticus and almost 35 times for P. lineatus when compared with subjects that were not exposed to the metal. This difference was statistically significant in the experiments for both species. The results indicate the high conservation of the MT gene structure, that allow the use of MT in environmental research.
Keywords: Genética; Peixes; Metalotioneína; Expressão gênica; Metais; Zinco; CIENCIAS BIOLOGICAS::GENETICA